Efficient millimetre‐wave imaging structure for detecting axially rotated objects. Issue 3 (18th January 2018) - Farsaee, Amir Ashkan; Kavehvash, Zahra; Shabany, Mahdi
Abstract : An efficient multi‐static millimetre‐wave (MMW) imaging system is proposed with the aim of obtaining the information of an axially tilted object. It is known that a multi‐static structure performs better than a mono‐static array in detecting the reflected signal from axially tilted surfaces due to the specular reflection. Still, no efficient multi‐static structure for the purpose of imaging tilted objects in view of the computational time, cost and image quality is proposed till now. The authors propose an efficient multi‐static MMW imaging system tackle this issue with the minimum number of antennae. Furthermore, the small number of antennae in the proposed design and the proposed fast reconstruction method considerably decrease the overall imaging time compared to conventional multi‐static structures, making it the technology of the choice for real‐time applications. Experimental results prove 2× and 1.4× improvement in the image quality (in terms of digital‐image‐correlation metric) compared to mono‐static and conventional multi‐static structures, respectively, and yet a great enhancement in the axial information, insofar as rotated targets are concerned.